1992
DOI: 10.1590/s0004-282x1992000300002
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic findings in acute cerebrovascular hemorrhage a prospective study of 70 patients

Abstract: In 1938, Asehenbrenner and Bodeehteis stated that intracranial lesions may be responsible for electrocardiographic abnormalities, but the first report of ECG changes in patients with cerebrovascular accidents was given by Byer, Ashman and Toth, in 1947 6. in 1954, Burch, Meyers and AbildskovS described a pattern of QT prolongation, abnormal T waves, and U waves which they considered distinctive of acute stroke. Since then, several reports about the prevalence and pathophysiology of ECG findings in different ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 22 publications
2
9
1
Order By: Relevance
“…It is remarkable that only one study reported QTc prolongation as the most frequently observed ECG abnormality, while others described it as an infrequently observed ECG abnormality [1,3,17,18]. One study observed that ectopic beats >10% were the most frequently observed ECG abnormality, in contrast to our and other studies [1,3,18].…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…It is remarkable that only one study reported QTc prolongation as the most frequently observed ECG abnormality, while others described it as an infrequently observed ECG abnormality [1,3,17,18]. One study observed that ectopic beats >10% were the most frequently observed ECG abnormality, in contrast to our and other studies [1,3,18].…”
Section: Discussioncontrasting
confidence: 84%
“…Other studies also found that sinus brady-/tachycardia and ST-T morphologic changes were frequently observed ECG abnormalities in the acute phase of intracerebral hemorrhage [1,3,17,18]. It is remarkable that only one study reported QTc prolongation as the most frequently observed ECG abnormality, while others described it as an infrequently observed ECG abnormality [1,3,17,18].…”
Section: Discussionmentioning
confidence: 96%
“…Other changes seen commonly include presence of a U wave, a Q wave, prolonged QTc intervals and large, flattened or notched T waves [15].…”
Section: Morphological Ecg Changesmentioning
confidence: 99%
“…ECG abnormalities have been described in the context of cerebrovascular accidents, most commonly consisting of QTc interval prolongation and ST-T segment abnormalities [1, 2]. Moreover, it is also known that subarachnoid hemorrhage can be associated with acute LV dysfunction [3].…”
Section: Discussionmentioning
confidence: 99%
“…Electrocardiographic (ECG) abnormalities and acute left ventricular (LV) dysfunction have been described in the context of cerebrovascular accidents [1, 2, 3]. Although there are rare case reports of patients with ECG changes consistent with an acute myocardial infarction, ECG patterns indicative of a localized myocardial infarction in the context of an intracranial hemorrhage are uncommon.…”
Section: Introductionmentioning
confidence: 99%